2008
DOI: 10.1186/1475-2875-7-151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urban agriculture on malaria vectors in Accra, Ghana

Abstract: To investigate the impact of urban agriculture on malaria transmission risk in urban Accra larval and adult stage mosquito surveys, were performed. Local transmission was implicated as Anopheles spp. were found breeding and infected Anopheles mosquitoes were found resting in houses in the study sites. The predominant Anopheles species was Anopheles gambiae s.s.. The relative proportion of molecular forms within a subset of specimens was 86% S-form and 14% M-form. Anopheles spp. and Culex quinquefasciatus outdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
133
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 27 publications
12
133
0
1
Order By: Relevance
“…The levels of urbanisation do not show a clear spatial pattern. However, some of the districts with the greater levels of urbanisation in central Uganda show some of the lowest levels of malaria incidence as observed in other African countries such as Ghana (Klinkenberg et al, 2008). Figure 3 illustrates the location of the climate-influenced regions obtained through WMVC.…”
Section: Resultsmentioning
confidence: 97%
“…The levels of urbanisation do not show a clear spatial pattern. However, some of the districts with the greater levels of urbanisation in central Uganda show some of the lowest levels of malaria incidence as observed in other African countries such as Ghana (Klinkenberg et al, 2008). Figure 3 illustrates the location of the climate-influenced regions obtained through WMVC.…”
Section: Resultsmentioning
confidence: 97%
“…Mosquito larval collections were performed between the May 9 and 30, 2008. Eight breeding sites within an area of 30 km 2 in the Greater Accra region were located by searching for water bodies in areas known to harbor A. gambiae (47). Larvae were reared to adults at the Biotechnology and Nuclear Agriculture Research Institute, Accra.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, a cross-sectional study in Ghana's capital, Accra, where there were no obvious confounding factors, also revealed significantly higher (P=0.008) malaria incidence among children living near urban agriculture (16.4 %) than those living in solely residential or industrial areas (11.4 %) (Klinkenberg et al 2005). The link between irrigated urban agriculture and malaria in Accra was made more direct through the study of Klinkenberg et al (2008), where trained (and brave) personnel in three urban agriculture and three non-urban agriculture areas captured mosquitoes upon landing on their exposed legs at night. Not only did about three times as many A. gambiae adults bite urban agriculture participants (urban agriculture: geometric mean = 8.1 [5.1,13.0,CI 90 ] bites per person per night; residential/industrial=2.8 [1.8, 4.3]) but also the entomological inoculation rate, which combines the rate of these bites and the frequency of Plasmodium in the mosquitoes, was markedly higher (19.2 cf 6.6-confidence intervals not reported).…”
Section: Malaria and Urban Agriculturementioning
confidence: 98%
“…The larval stages of mosquitoes develop in stagnant water, hence the concern about irrigated urban agriculture offering a breeding-ground for vectors. The contentious issue of urban agriculture and malaria has been well investigated on the African continent, where malaria well and truly has its greatest global impact (Klinkenberg et al 2008;Matthys et al 2006;Stoler et al 2009). In Dar es Salaam, Tanzania, Dongus et al (2009) found that location within lowland areas, proximity to a river, and presence of relatively impervious soils were statistically significant (P<0.05) geographic predictors of the presence of anopheline larvae; and seedbed type, mid-size gardens, irrigation by tap water, rain-fed agriculture, and cultivation of leguminous crops or fruit trees were significant negative predictors.…”
Section: Malaria and Urban Agriculturementioning
confidence: 99%
See 1 more Smart Citation